Pemanfaatan Terapi Aquaponik Sebagai Strategi Peningkatan Kesehatan dan Gizi Lansia - Ramdika, Sari Bema; Ningsih, Windi Indah Fajar; Prautami, Erike Septa (JPM: Jurnal Pengabdian Masyarakat, 2025)
The increase in life expectancy in Indonesia has resulted in a growing elderly population (older adults) who face various health, nutritional, and psychosocial challenges, particularly those living in social care institutions. One alternative approach to address these issues is aquaponic therapy, an integrated system of fish farming and hydroponic cultivation that serves not only as a source of nutritious food but also as an environmental therapy medium. This community service program aimed to improve the knowledge, skills, and quality of life of the elderly through aquaponic training and aquaponic therapy at Boarding Care Noor Fatimah, Palembang. The program consisted of two main stages: (1) aquaponic training, including the delivery of basic concepts and hands-on practice in preparing planting media, cultivating water spinach seedlings, and stocking fish fry; and (2) aquaponic therapy, which involved simple activities such as feeding fish, watering plants, harvesting vegetables, and participating in motivational sessions guided by a psychologist. Evaluation was conducted qualitatively through observation and interviews to assess the participation, enthusiasm, and perceptions of both elderly participants and caregivers. The findings indicate that aquaponics training effectively enhanced older adults’ comprehension of the fundamental principles and benefits of the system. Participants demonstrated greater awareness of the importance of maintaining health through healthier dietary practices derived from aquaponic produce. Moreover, aquaponics therapy promoted engagement in light physical activities and nurtured a sense of responsibility in caring for both plants and fish. From an emotional perspective, participants reported increased levels of happiness, satisfaction, and pride, particularly when sharing and consuming the harvest collectively. The main challenges identified were memory limitations and physical constraints of the elderly, as well as limited caregiver availability, which highlighted the need for capacity-building and simplified maintenance systems. Overall, the program not only provided educational and psychosocial benefits but also demonstrated potential to strengthen food security and institutional independence in a sustainable manner.